Weight Gain Comparison between Heifers Fed Colostrum or Whole Milk until Weaning - Helayel, Michel Abdalla; de Souza, Luciana Aparecida; do Sacramento Conceição, Jorge Henrique; Nogueira, Vivian de Assunção; Caldas, Saulo Andrade; da Cunha, Isabelle Magalhães; Chenard, Malina Galindo; Leonardo Pereira, Raphael Delecrodi; de Souza Ramos, Luiz Filipe Cabral; Balistrieri Dias, Mirela (Acta Scientiae Veterinariae, 2019)
Background: The milk-feeding phase, wherein whole milk is the natural food, is critical to calf development, health, and vitality. However, feeding milk to calves is costly in the rearing system because the milk supplied to calves is not sold. In farms in which the average production is high, excess colostrum and transitional milk are produced that are used to feed calves until weaning. The objective of this study was to evaluate the performance of heifers exclusively fed colostrum (including transitional milk) or raw whole milk. Materials, Methods & Results: Immediately after their birth, 83 ear-tagged healthy Holstein Friesian heifers adequately receiving the initial colostrum were separated into two experimental groups. Group 1 (n = 34) was fed only fresh whole milk and group 2 (n = 49) was fed only colostrum diluted in water at a 2:1 ratio. Colostrum was removed from cows until the fifth day after birth and was stored in sanitized disposable plastic bottles, stored in a freezer at -20°C and before administration, the colostrum was thawed. Liquid diets were administered using a bottle twice a day during the first month, namely 2 L in the morning and 2 L in the afternoon. During the second month, the heifers were fed 4 L once a day in the morning. The heifers had access to an enclosure with fodder, in addition to concentrate specifically for heifers, which was placed in an individual trough daily. The leftovers were weighed at the end of the afternoon. The heifers were abruptly weaned when they reached a daily intake of 1 kg of concentrate. The heifers were individually weighed at birth and at 30, 60, 90, 120, 150, and 180 days. The average weights were 40.4, 54.1, 74.5, 95.1, 108.2, and 126.1 kg in group 1 and 45.4, 58.4, 78.2, 95.9, 110.8, and 125.1 kg in group 2. The use of diluted colostrum was satisfactory as it resulted in similar weight gains. Discussion: Feeding milk to calves is one of the most cost-increasing factors to a dairy farm because the total milk volume fed to animals at this stage is not sold and results in a large loss in income for the farmer. Calf management during the milk-feeding phase is of the utmost importance, especially in the first days after birth, to ensure the development of the systemic immune response of animals. The performance of these animals in the first months affects their subsequent development. Whole milk is commonly used to feed calves for 8 to 12 consecutive weeks. However, whole milk can be replaced by a good substitute, such as colostrum and transitional milk. The aim of this study was to show that these substitutes are effective alternatives for calf development and cost reduction. The weight gain of animals fed diluted colostrum was similar to that of animals fed only whole milk, which corroborates the results of previous studies on the development of calves treated with colostrum-based liquid diet, fermented or not, with and without additives. Those studies reported favorable growth rates in comparison with the traditional production system as a result of higher dietary protein levels in colostrum-based diets. The availability of roughages and concentrates should be initiated during the milk-feeding phase, as it is fundamental for rumen development, helps in early weaning and reduces expenses during this period. Replacing whole milk with colostrum and transitional milk for feeding calves, stimulating roughage, and concentrating intake can result in significant savings in the rearing system.